Failure of riverbank protection structure and remedial approach: A case study in Suraburi province, Thailand. (September 2018) - Udomchai, Artit; Hoy, Menglim; Horpibulsuk, Suksun; Chinkulkijniwat, Avirut; Arulrajah, Arul
Abstract: This paper presents the case study of a collapsed riverbank protection structure, located in the curvature of the watershed along the Pasak river in Saraburi province, Thailand. Although efforts have been made to twice rehabilitate this collapsed structure, the rebuilt protection structures were unstable to prevent progressive collapse damage and the causes of their failure remained elusive. The project team was engaged to carried out the site investigation and finite element analysis prior to providing the remedial approach on the collapsed structure. The outcome from this study reveals that the natural disaster events were the main causes of the structure failure. During the rainy season, water flowed into the river from upstream farmlands by crossing the backfill of the riverbank protection structure. Seepage forces were thus developed in the direction of inflows, which resulted in reduced stability of the riverbank protection structure. Furthermore, the strong currents in the river continuously scoured the banks, undermining the natural slope in front of the riverbank protection structure, resulting in soil erosion in the passive zone and instability of the protection structure. Based on these two causes of failure, a remedial solution was devised using a new bored pile riverbank protection structure with the usage of geocomposites and ripraps. Geocomposites and ripraps were installed at the back and front of the bored pile walls to relieve the structure from seepage forces and to prevent soil erosion, respectively. An adequate factor of safety against the external and internal failure of the new riverbank protection structure was verified by finite element modeling and the results confirmed that the structure was safe. Highlights: A case study of a collapsed riverbank protection structure Site investigation and FEM indicated that failure occurred due to natural disaster. A new bored pile riverbank protection structure with the usage of geocomposites An adequate factor of safety of the new structure was verified by FEM.